The mechanism of discriminative aminoacylation by isoleucyl-tRNA synthetase based on wobble nucleotide recognition - Bingyi Chen; Fang Yi; Zhiteng Luo; Feihu Lu; Hongwei Liu; Siting Luo; Qiong Gu; Huihao Zhou (Nature Communications)
Abstract The faithful charging of amino acids to cognate tRNAs by aminoacyl-tRNA synthetases (AARSs) determines the fidelity of protein translation. Isoleucyl-tRNA synthetase (IleRS) distinguishes tRNAIle from tRNAMet solely based on the nucleotide at wobble position (N34), and a single substitution at N34 could exchange the aminoacylation specificity between two tRNAs. Here, we report the structural and biochemical mechanism of N34 recognition-based tRNA discrimination by Saccharomyces cerevisiae IleRS (ScIleRS). ScIleRS utilizes a eukaryotic/archaeal-specific arginine as the H-bond donor to recognize the common carbonyl group (H-bond acceptor) of various N34s of tRNAIle, which induces mutual structural adaptations between ScIleRS and tRNAIle to achieve a preferable editing state. C34 of unmodified tRNAIle(CAU) (behaves like tRNAMet) lacks a relevant H-bond acceptor, which disrupts key H-bonding interactions and structural adaptations and suspends the ScIleRS·tRNAIle(CAU) complex in an initial non-reactive state. This wobble nucleotide recognition-based structural adaptation provides mechanistic insights into selective tRNA aminoacylation by AARSs.